2003
DOI: 10.1046/j.1439-037x.2003.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Wheat Straw Soil Surface Coverage on Weed Flora in Vicia faba Crops

Abstract: The crop system implemented on organic farms requires that crop residues are incorporated into the soil following the end of wheat cultivation. This system leads to a reduction in soil moisture and the creation of favourable conditions for the emergence of weeds. In contrast, covering the soil with 60 % crop residues was found to maintain soil moisture and lead to a reduction in dry weed mass, population density and population frequency as well as a reduction in population diversity, regardless of the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 26 publications
1
56
0
7
Order By: Relevance
“…Weed biomass increased by at least 22 % (P < 0.01) at 9 WAP and 13 % (P < 0.05) at 13 WAP under mulching. Consequently, it would appear from our observations that the retention of maize residue rather than suppressing weeds as is widely reported (Bilalis et al, 2003;FAO, 2010) increased the emergence of weed seedlings and their subsequent survival rate compared to un-mulched plots.…”
Section: Effects Of Mulch Ratesupporting
confidence: 59%
See 2 more Smart Citations
“…Weed biomass increased by at least 22 % (P < 0.01) at 9 WAP and 13 % (P < 0.05) at 13 WAP under mulching. Consequently, it would appear from our observations that the retention of maize residue rather than suppressing weeds as is widely reported (Bilalis et al, 2003;FAO, 2010) increased the emergence of weed seedlings and their subsequent survival rate compared to un-mulched plots.…”
Section: Effects Of Mulch Ratesupporting
confidence: 59%
“…Since temperature and light are important cues for seed dormancy and germination for most annual weed species, shading of the soil surface by the mulch early in the season before the sorghum canopy had fully formed resulted in suppression of weed emergence and growth. Bilalis et al (2003) observed that both weed density and biomass decreased with increased wheat residue mulch on an organic farm in Greece. In Zambia, Gill et al (1992) found that 5 t ha -1 of grass (Cynodon species) residues significantly reduced weed biomass in the first 42 days of maize growth in a MT system.…”
Section: Effects Of Mulch Ratementioning
confidence: 96%
See 1 more Smart Citation
“…The suppression of weeds at the early growth stage was important for successful weed control by cover crops (Uchino et al, 2005). Bilalis et al (2003) indicated that there was a significant and negative correlation between percentage of soil cover by crop residue and weed DW. Peachy et al (1999) and Teasdale and Mohler (2000) also reported that the degree of weed suppression depended on soil coverage of vegetation.…”
Section: Competition For Lightmentioning
confidence: 99%
“…Mulsa kimia sintetis meliputi bahan plastik. Mulsa jerami padi dapat mengurangi fluktuasi suhu, dan meningkatkan kelembaban dan mengurangi evapotranspirasi (Bilalis ., 2002;Doring 2006;Mayun, et al et al, 2007). Zeolit merupakan padatan anorganik berwarna kebiru-biruan, bersifat basa sehingga dapat menetralkan tanah, mempunyai permukaan yang luas dan sangat berpori sehingga mempunyai kemampuan mengikat air (Barrer, 1982;Dyer, 1988;Prayitno ., 1989;Meier et al et al et al ., 1996;Bachrein ., 1998;Herawati, 2001) Warna mulsa plastik akan menentukan sifat cahaya yang dipantulkan, diserap dan diteruskan (Mahrer, 1979;Elnizar, 2004 Gordon et al, 2010, Sukirno, 1983Purwowidodo, 1983;Fauzan, 2002;Widyasari et al, 2011, Gordon et al, 2010Franquera, 2011;Zhao et al, 2012, Navratilova dan Prijono, 2013Gordon et al, 2010;Darmawan, 2014;Azad, Hasan dan Parvizi, 2015;Mutetwa dan Mutaiti, 2014;Wisudawati et al, 2016).…”
Section: Pendahuluanunclassified